Distribution of sul genes and their variants in uropathogenic Escherichia coli isolated from two hospitals of Sabah (Asian Journal of Medical and Biological Research, 2016)
Sulphonamides resistant strains are highly prevalent in uropathogenic Escherichia coli (UPEC) isolates. Sul genes encode sulphonamide resistance and are present on transferrable plasmids. Integrons (IGNs) are genetic elements containing integrase gene, attl site and gene cassettes which carry multiple antibiotic resistant genes. Class 1 integrons have been extensively studied because these were most prevalent among clinical isolates. In this study, UPEC isolates were determined for the antibiotic susceptibility patterns to four antibiotics commonly used for urinary tract infections, which include co-trimethoxazole (TMP-STX). Distribution of sul genes and integrase1 gene (intI1) was studied in TMP-STX resistant UPEC isolates by using multiplex polymerase chain reaction (mPCR). Sul genes variants were investigated by DNA sequencing of the whole open reading frame of sul1 and sul2 genes and PCR product of sul3 gene. Sul1, sul2 and sul3 genes were prevalent in 37 (24.7%) of 150 UPEC isolates. IntI1 is positive in 22 sul genes positive isolates. Of six isolates positive with sul2 genes, sul2(a) and sul2(b) variants, which were described in the previous study, in the four isolates and the two isolates respectively were observed. This is the first mPCR which investigates the prevalence of three sul genes and intI1 in the UPEC clinical isolates from two hospitals of Sabah.Asian J. Med. Biol. Res. June 2016, 2(2): 213-220